THE FEATURES OF THE PROPAGATION OF ELASTIC WAVES IN ISOTROPIC MEDIA AT HIGH AND ULTRA-HIGH PRESSURES - Guliyev, H. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Studies of problems of the propagation of elastic waves in the geological medium constitute the scientific basis of the processing and interpretation of dataset of seismic exploration and seismological works. Objective. Creation of a more grounded theoretical basis of the geomechanical interpretation of various groups of geophysical observational and experimental data. Methodology. Nonclassical-linearized approach of non-linear elastodynamics. Linear and nonlinear small and large initial deformations are taken into account. The strain processes are described applying various elastic potentials. Results. Analytical dependences of the parameters of pressure and velocities of propagation of elastic waves on deformations without additional linearization are obtained within the framework of various versions of the theory of small and initial deformations using the quadratic and elastic potentials of the Murnaghan type. Scientific novelty. It is established that there are critical values of deformation while reaching them elastic pressure and shear waves with true velocity cannot propagate in uniformly deformed elastic isotropic media. The quantitative values of the critical values of deformations for pressure and shear waves differ, and essentially depend on the applied elastic potentials. Practical significance. The obtained analytical dependences allow synthesizing the true values of the elastic parameters of the deformed media from seismic exploration and seismological dataset. The establishment of critical deformations for velocities of pressure and shear waves will make it possible to suggest differential criteria of the distribution of elastic parameters in theoretical models of the Earth in its various structural elements as a whole and separately.
Keywords: Nonlinear elastodynamics; elastic waves; initial deformation; velocities of pressure and shear waves